Ancient civilizations. Almanac - Knight, Judson; McConnell, Stacy A.; Baker, Lawrence W. (Detroit UXL, 1999)
Provides historical information and interpretation on ancient civilizations in Egypt, Mesopotamia, Asia Minor, China, Africa, Israel, and elsewhere.
v. 1. Egypt--India -- China--Rome.
Includes bibliographical references and index.
Keywords: Civilization, Ancient -- Juvenile literature; Civilization, Ancient -- Miscellanea -- Juvenile literature; Civilization, Ancient